MODERN APPROACHES TO THE SYSTEM OF TEACHING AND LEARNING A FOREIGN LANGUAGE (IN THE CASE OF BLIND PEOPLE WITH DISABILITIES) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article deals with the education of needy children with special support, including children with visual impairments, and work to eliminate their impairments. It focuses on the problems encountered in learning a foreign language by people with disabilities (the blind) and their solutions.